2021
DOI: 10.51300/jidm-2021-35
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stereotypical music on the customer selection of wine in an online environment

Abstract: The digital transformation of marketing leads to new forms of interaction with consumers. It has been established and well known that auditory stimuli generally affect human behavior. However, in the field of sensory marketing, only limited attention has been paid to the role and effects of audition in online marketing. In this research, we will further explore how sound influences consumer product selection in a digitalized setting. We have designed and performed an experiment in which respondents in a websho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…For example, North et al ’s (1997, 1999) classic study of the impact of French vs German music on wine sales in a British supermarket (first published in top science journal Nature ), was based on just 82 transactions/customers (44 of whom agreed to be interviewed about why they had chosen the wine that they had after leaving the tills; see also Hultén, 2012, for another very small sample store study). Nevertheless, the latest research has demonstrated similar cross-modal effects of French vs German background music on online wine sales (Damen et al , 2021; though see also Heryet, et al ., submitted).…”
Section: Questioning the “Meaning” Of Marketing Studies Involving Atm...mentioning
confidence: 94%
“…For example, North et al ’s (1997, 1999) classic study of the impact of French vs German music on wine sales in a British supermarket (first published in top science journal Nature ), was based on just 82 transactions/customers (44 of whom agreed to be interviewed about why they had chosen the wine that they had after leaving the tills; see also Hultén, 2012, for another very small sample store study). Nevertheless, the latest research has demonstrated similar cross-modal effects of French vs German background music on online wine sales (Damen et al , 2021; though see also Heryet, et al ., submitted).…”
Section: Questioning the “Meaning” Of Marketing Studies Involving Atm...mentioning
confidence: 94%
“…Music can, for instance, be part of a business model: auditory stimuli are deliberately used to encourage sales. After all, music can affect consumer choices and can be used to nudge the consumer (Damen et al, 2021;North et al, 1999;Spence and Zampini, 2006), or can help to encourage (positive) brand awareness (Fraser, 2014). Also, music can be owned in terms of intellectual property.…”
Section: Tough Musicmentioning
confidence: 99%
“…In the real-world, high-tempo music may bemore likely to encourage the consumer to purchase products than any change to the ambient lighting (Hagtvedt and Brasel, 2016). The selection of products by the consumer can sometimes be strongly influenced by auditory stimuli (stereotypical French and German music) in a web shopping environment (Damen et al, 2021), here matching the findings reported previously showing that auditory sensory cues affect consumers' emotion and purchase decisions in the store atmosphere (Yalch and Spangenberg, 2000;Helmefalk and Hultén, 2017). Auditory cues can be used to bias a consumer's visual product search, attention, selections and decision-making (Knoeferle et al, 2016).…”
Section: Perceived Auditory Stimulationmentioning
confidence: 99%